Molecular Dynamics Simulation Of Thermal Processes For Selected Nano-Structures - Min, Tjun Kit (2018)
The core premise of this thesis is the adoption of molecular dynamics (MD) in simulating and measuring three different nanoscale systems. namely (i) epitaxial graphene growth on 6H-SiC (0001) surface induced by simulated annealing, (ii) free-standing silicene subjected to extensive thermal heating, and (iii) wurtzite ZnO slab which is subjected to simulated annealing. Epitaxial growth of graphene on the (0001) surface of 6H-SiC substrate is simulated via molecular dynamics using LAMMPS code. A specially designed protocol to reconstruct the surface via a simulated annealing procedure, is prescribed to simulate the epitaxial graphene formation on the substrate surface. Two empirical potentials, the Tersoff potential and the TEA potential are used in the MD simulations to investigate and compare the growth mechanisms resulted. Results obtained from MD simulated in this thesis show that TEA potential is more accurately in describing the growth process of graphene formation, in which the result is generally more physical and realistic. Graphene is shown in the MD simulation using TEA potential to be accurate at an annealing temperature of